Survival Strategy in Accepting Threats And Opportunities At Pesantren Assunniyah Kencong Jember Indonesia - Muhammad Yasaruddin bin Yassir; Ahmad Halid; Dede Husni Mubarok (IJIBS, 2023)
This article reveals very interesting things about the survival strategy of Islamic boarding schools in facing challenges and filling opportunities for educational progress at the Assunniyah Kencong Jember Islamic boarding school. therefore this research uses quantitative methods with an ethnographic study approach to describe the way they think, live, and behave in developing Islamic boarding schools. The research problem is how is the Islamic Boarding School Education Survival Strategy in Facing Challenges and Filling Opportunities for Educational Progress at the Assunniyah Kencong Jember Islamic Boarding School. The survival strategy of the Assunniyah Jember Islamic boarding school in facing challenges and filling opportunities for educational progress uses the TOWS analysis model: Threats, Opportunities, Weaknesses, and Strengths. So that the use of this TOWS analysis at the Assunniyah Jember Islamic boarding school can be able to face challenges and fill opportunities and have the strength of tradition in developing Islamic boarding school education programs into a sporadic educational model.